Positive Trend Correlation of Jokowi's Social Media Exposure Regarding The Electability of #probowopresiden2024 - Yudi Daherman; Ivan Taufiq (ULTIMA Comm, 2023)
The political contestation of the 2024 presidential election in Indonesia has shown the influence of the electability of each candidate. One of them is through President Jokowi's social media, giving a positive trend for several candidates, followers give signs of support to the 2024 presidential candidates. Signs on social media have become a new trend for people in cyberspace to discuss it. The purpose of this study, how President Jokowi through his social media provides a positive trend for the 2024 presidential candidates, through new signs on social media becomes prevalent because the current president should not provide support to one of the candidates, but because the 2 presidential candidates are currently still officials in the government. President Jokowi's support on social media for presidential candidate Parbowo, who is currently the Minister of Defence, has been read by the signs given on Jokowi's social media. This will make a positive trend for Prabowo to get attention for the public. Through big data analysis on social media Instagram and twitter. The click bait media questioned where is Jokowi's support going? To Ganjar or Prabowo? The signs analysed through big data show that Jokowi is playing a role in the two 2024 presidential contenders. The sign #prabowopresident2024 received positive sentiment on facebook, Instagram and tiktok.